Mechanical and wear properties of palm oil fuel ash reinforced aluminum metal matrix composite - Ma, H.L.; Sujan, Debnath; Kyaw, T.T.; Oo, Zeya (American Institute of Physics, 2013)
The metal matrix composites consist of unique properties that make the materials become more attractive in a variety of industrial applications. Palm oil fuel ash (POFA) is produced from the burning of palm oil shell and husk fiber in generation plant boiler for energy generation that serve the palm oil extraction purposes. It has been discarded as agricultural industrial wastes. However, POFA contains a high percentage of hard silica (SiO2) which therefore makes it extremely valuable for manufacturing high strength composites materials including electronic, ceramic, polymer, glass, and construction materials industries. In this paper, it evaluated the use of Palm Oil Fuel Ash (POFA) particles in the production of Al-MMC in order to strengthen the properties of the base metal. Particle-size of 75 and different volume fraction of Palm Oil Fuel Ash (POFA) particles (5%, 10% and 15%) particulate-reinforced Al-MMCs are fabricated by using the stir casting method and tested for mechanical properties. The microstructure of the fabricated composite material are also studied and analyzed in this study. It was observed that the tensile and impact strength and wear resistance of the composite increased substantially as the volume fraction of reinforcing particle increased.